Community Empowerment through IoT-Based Smart Poultry Farming and Product Innovation in Kampung Ilmu - Prio Handoko; Ratna Safitri; Teddy Mohamad Darajat (SWAGATI : Journal of Community Service, 2026)
Community empowerment requires the integration of appropriate technology and community capacity building to improve productivity and economic competitiveness. This community service program was conducted at Kampung Ilmu, Purwakarta, Indonesia, to address manual poultry farming practices, low hatchability rates, and limited product competitiveness. The program aimed to empower the community through the implementation of Internet of Things (IoT)-based poultry technology and product innovation. The implementation stages included needs assessment, field observation, prototype development, implementation, training, mentoring, and evaluation involving lecturers, students, and community partners. The program produced an IoT-based smart poultry house, a smart egg incubator, modular poultry housing, and environmentally friendly packaging for eggs and vegetables. Evaluation results showed increased community knowledge and skills in poultry management, packaging techniques, and product branding after the mentoring activities. The implementation of appropriate technology improved farming efficiency, strengthened community capacity, and enhanced the competitiveness of local products. These findings indicate that integrating IoT technology with product innovation can effectively support sustainable rural community empowerment.